2004
DOI: 10.1128/aem.70.9.5493-5502.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the N -Acyl Homoserine Lactone-Dependent Quorum-Sensing System in Rhizosphere Pseudomonas putida WCS358 and Cross-Talk with the Stationary-Phase RpoS Sigma Factor and the Global Regulator GacA

Abstract: Quorum sensing is a cell population-density dependent regulatory system which in gram-negative bacteria often involves the production and detection of N-acyl homoserine lactones (AHLs). Some Pseudomonas putida strains have been reported to produce AHLs, and one quorum-sensing locus has been identified. However, it appears that the majority of strains do not produce AHLs. In this study we report the identification and regulation of the AHL-dependent system of rhizosphere P. putida WCS358. This system is identic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
85
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 39 publications
9
85
2
Order By: Relevance
“…The neighbour-joining phylogenetic trees resulting from the predicted GacS and GacA protein sequences of H. anticariensis both show that the sequences from the halophilic strains cluster together in a separate group from the Pseudomonadaceae and Enterobacteriaceae (Fig. S1), which concurs to a great extent with the topology of the GacA-protein-based tree found by de Souza et al (Bertani & Venturi, 2004) and Serratia plymuthica (Ovadis et al, 2004). Nevertheless, AHL production was not fully restored when the gacS gene was complemented in trans in H. anticariensis FP35 T .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The neighbour-joining phylogenetic trees resulting from the predicted GacS and GacA protein sequences of H. anticariensis both show that the sequences from the halophilic strains cluster together in a separate group from the Pseudomonadaceae and Enterobacteriaceae (Fig. S1), which concurs to a great extent with the topology of the GacA-protein-based tree found by de Souza et al (Bertani & Venturi, 2004) and Serratia plymuthica (Ovadis et al, 2004). Nevertheless, AHL production was not fully restored when the gacS gene was complemented in trans in H. anticariensis FP35 T .…”
Section: Discussionsupporting
confidence: 70%
“…It has been suggested that the three systems, GacS/GacA, QS and RpoS, interact in a complex regulatory network, which is probably modulated according to environmental conditions. In some Pseudomonas species the QS and RpoS systems regulate each other whilst GacA positively regulates the production of AHLs (Bertani & Venturi, 2004). A third pathway begins with the GacS/GacA TCS triggering the transcription of one or several genes that encode small untranslated RNAs (sRNAs) (Bejerano-Sagie & Xavier, 2007;Lapouge et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A role of rpoS in antibiotic production has been reported (Sarniguet et al, 1995;Suh et al, 1999), but not for regulating PCN production. The inhibitory effect of RpoS on quorum sensing and pyocyanin in P. aeruginosa (Whiteley et al, 2000) or of PsrA and RpoS on quorum sensing in P. putida WCS358 (Bertani & Venturi, 2004) is the opposite of what we observed for strain PCL1391. Surprisingly, RpoS was previously shown not to be involved in homoserine lactone production by P. putida WCS358 (Kojic et al, 1999).…”
Section: Discussioncontrasting
confidence: 50%
“…Surprisingly, RpoS was previously shown not to be involved in homoserine lactone production by P. putida WCS358 (Kojic et al, 1999). This is interesting for our study, because in the latter case P. putida was grown in minimal medium (Kojic et al, 1999), whereas in the most recent study P. putida was grown in the complex LB medium (Bertani & Venturi, 2004). In P. aeruginosa, the effect of quorum sensing on rpoS transcription in P. aeruginosa is mild (Schuster et al, 2004).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation